2005
DOI: 10.1002/cncr.20936
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic thyroid carcinoma

Abstract: BACKGROUNDAnaplastic thyroid carcinoma (ATC) is rare but is one of the most aggressive human malignancies. Several prognostic factors have been observed in patients with ATC, and some experts advocate aggressive multimodal therapy in selected patients. However, it is unclear whether such an approach significantly improves survival. The authors analyzed prognostic factors and treatment outcomes in patients with ATC reported in the National Cancer Institute's Surveillance, Epidemiology, and End Results data base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
183
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(213 citation statements)
references
References 33 publications
12
183
0
4
Order By: Relevance
“…Although it accounts for only 1.7% of thyroid carcinomas in the United States, it is responsible for up to 39% of thyroid carcinoma deaths. Prognosis is dismal: overall cause-specific mortality rate is 68.4% at 6 months and 80.7% at 12 months [1]. As in our patient, common presenting symptoms of ATC include laryngeal, tracheal, and esophageal obstruction.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Although it accounts for only 1.7% of thyroid carcinomas in the United States, it is responsible for up to 39% of thyroid carcinoma deaths. Prognosis is dismal: overall cause-specific mortality rate is 68.4% at 6 months and 80.7% at 12 months [1]. As in our patient, common presenting symptoms of ATC include laryngeal, tracheal, and esophageal obstruction.…”
supporting
confidence: 46%
“…The study found the median survival following diagnosis of ATC to be 5 months, with a median 1-year survival of 20%, making it one of the most aggressive solid tumors to affect humans [2]. The median age of onset is 71.3 years (SD 12.7 years) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms can be related to invasion of tumor to neighboring structures such as recurrent laryngeal nerve (RLN), parasympathetic chain (causing Horner's syndrome), or even carotid arteries (causing stroke). About 40% of patients usually present with lymphadenopathy and up to 43% have distant metastasis, most commonly to the lung followed by bone and brain at the time of diagnosis [98].A variety of previous studies have evaluated prognostic factors of ATC [99][100][101][102]. These prognostic factors include patients' age, tumor size, and clinical stage.…”
mentioning
confidence: 99%
“…Kebebew et al analyzed data from the SEER database and they estimated that the age under 60 and the intrathyroidal ATC location are the two main factors for expecting longer survival [4]. Our patient was a 66-year-old woman and there have been found metastases in the lungs, what indicated a poor progno- …”
Section: Discussionmentioning
confidence: 71%
“…It is worth noting, that although this type of cancer is a rare neoplasm, the mortality rate is above 90% and it is the cause of 14-39% deaths of patients with the thyroid cancer [4]. One-year and 5-year relative survival rates are estimated to be 10-20% and 4.6-5.4% respectively [3,5].…”
Section: Discussionmentioning
confidence: 99%